2021
DOI: 10.21203/rs.3.rs-257472/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Chloroplast Genome Evolution of Venus Slipper (Paphiopedilum): IR Expansion, SSC Contraction, and Highly Rearranged SSC Regions

Abstract: Background: Paphiopedilum is the largest genus of slipper orchids. Previous studies showed that the phylogenetic relationships of this genus are not well resolved, and sparse taxon sampling documented inverted repeat (IR) expansion and small single copy (SSC) contraction of the chloroplast genomes of Paphiopedilum. Here, we sequenced, assembled, and annotated 77 plastomes of Paphiopedilum species. The phylogeny based on the plastome resolved the relationships of the genus except for the phylogenetic position o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Chloroplast genomes have been used to address the chloroplast genome evolution, patterns and rates of nucleotide substitutions and phylogenetic relationships among land plants [20]. Chloroplast is a kind of vital organelle that can transform light energy into chemical energy in green plants [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast genomes have been used to address the chloroplast genome evolution, patterns and rates of nucleotide substitutions and phylogenetic relationships among land plants [20]. Chloroplast is a kind of vital organelle that can transform light energy into chemical energy in green plants [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Inverted repeat regions are considered the most conserved regions. The size variations in cp genomes occur due to expansion/contraction of IRs and single copy regions 76,90,91 . The four junctions (JLA, JLB, JSA, and JSB) between the single copy regions (LSC, SSC) and IRs (IRA, IRB) in cp genomes of D. serrulata, D. cinnabari, and others were comprehensively assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Inverted repeat expansion and contraction were mostly associated with cp genome size variation ( McCoy et al, 2008 ; Wu et al, 2009 ). Expansion and contraction in IRs of chloroplast genomes have been widely reported in various kinds of plants ( Krause, 2011 ; Weng et al, 2014 ; Schwarz et al, 2015 ; Shrestha et al, 2019 ; He et al, 2020 ; Guo et al, 2021 ). We also found that cp genomes in the 34 Triticeae species exhibited obvious different IR sizes.…”
Section: Discussionmentioning
confidence: 99%